Novel brain biomarkers of obesity in young adult women based on statistical measurements of white matter tracts - José Gerardo Suárez-García; María Isabel Antonio-de la Rosa; Nora Coral Soriano-Becerril; Javier M. Hernández López; Martín Rodolfo Palomino-Merino; Benito de Celis-Alonso (PLoS ONE, 2025)
Objective Novel brain biomarkers of obesity were sought by studying statistical measurements on fractional anisotropy (FA) images of different white matter (WM) tracts from young adult women. Methods Tract measurements were chosen that showed differences between two groups (normal weight and overweight/obese) and that were correlated with BMI. From these measurements, a simple and novel process was applied to select those that would allow the creation of models to quantify and classify the state of obesity of individuals. The biomarkers were created from the tract measurements used in the models. Results Positive correlations were found between WM integrity and BMI, mainly in tracts involved in motor functions. From these results, two models were built to quantify and classify obesity status, whose regression coefficients formed the novel proposed obesity associated brain biomarkers. Conclusion A process for the selection of tract measurements was proposed, such models were built to determine the obesity status of subjects individually. From these models, novel brain biomarkers associated with obesity were created. These results generate new knowledge in the field, intended to be used in the future in the clinical environment as a prevention and treatment tool for brain changes associated with obesity. Significance After studying young adult women, results opposed some of the previous results reported in literature. These consisted of positive correlations between WM integrity and obesity mainly in tracts involved in motor functions. Novel brain biomarkers of obesity were also proposed, formed by the regression coefficients involved in precise models of quantification and classification of obesity status. All this allows the generation of new knowledge and its probable subsequent clinical application.